Development of solid acid catalysts for biodiesel production from high free fatty acid feedstock / Yahaya Muhammad Sani - Yahaya, Muhammad Sani (2015)
Numerous energy crises have been confronting the world due to excessive utilization of the world's depleting oil reserves by the ever-increasing human population. Concerns such as deteriorating health standards and environmental degradations have led to the search for sustainable biofuel alternatives. However, the recent nose-diving of the Brent crude oil price makes the search for sustainable catalysts more arduous. Consequently, the present study investigated two distinct catalytic routes for producing biodiesel from a cheap feedstock, which could have competitive edge with fossil diesel. Firstly, the study explored the potentials of converting wastes from oil palm biomass such as empty fruit bunch (EFB), palm frond (PTF), spikelet (PTS) and waste fruit (WPF) into sulfonated mesoporous solid acids via carbonization-sulfonation method. Brunauer-Emmet-Teller (BET), powder X-ray diffraction (XRD), Energy dispersive X-ray (EDX), and field emission scanning emission microscopy (FE-SEM) analyses elucidated the structural and textural properties of the catalysts. Further, Fourier transform-infrared (FT-IR) spectroscopy and titrimetric analyses measured the strong acid value and acidity distribution of the materials. These evidenced large mesopore volumes, large surface areas, uniform pore sizes, and high acid densities on the catalysts. The catalytic activity exhibited in esterifying used frying oil (UFO) containing high (48%) free fatty acid (FFA) further confirmed these properties. Interestingly, sEFB/300 and sPTS/400 converted more than 98% FFA into fatty acid methyl esters (FAMEs). This is outstanding considering the lower reaction parameters of 3 h, 5:1 methanol-to-oil ratio, and moderate temperature range between 100 and 200 °C. Equally, the study delved into a process considered to have attained state-of-the art status; sulfated zirconia (SZ), which has been the subject of numerous reports since its discovery in 1979. The catalytic activity of SZ in esterifying FFA and transesterifying triglycerides iv (TG) simultaneously from high-FFA containing feedstocks into biodiesel has led to claims that SZ are superacids, or at least very strong acids. However, SZ has some inherent limitations such as slow reaction rates. Similarly, despite the numerous advantages of zeolite catalysts, microporosity hinders their industrial applicability for biodiesel production. Evidently, several reports on optimal preparative conditions that produced superacidic materials abound via carefully controlled procedures. Nonetheless, to date, no study has reported the effect of grafting zeolite on SZ for biodiesel production. Further, there is no information from open literature regarding biodiesel production over SZ doped with ytterbium, Yb. Consequently, this study investigated the prospects of combining mesoporous zeolite and SZ; and effect of doping SZ with Yb for biodiesel production. The study synthesized different composite catalysts that have potential to maximize activity and minimize adsorbate-induced surface reconstruction, with consequent reduction in net energy consumption. Remarkably, large mesoporosity, high amount, and dispersion of active sites on Yb-doped SZ ensured significant activity despite low specific surface area that was due to short aging period. However, different sulfation methods showed marginal effect on SZ. Interestingly, the catalyst achieved more than 99% conversion under moderate conditions. These findings will definitely help to further the biofuel central policy of replacing petrodiesel in the possible near future.